Salty summertime streams-road salt contaminated watersheds and estimates of the proportion of impacted species - Lauren Lawson; Donald A. Jackson (Canadian Science Publishing, 2021)
Road salt runoff is a leading cause of secondary freshwater salinization in north temperate climates. Increased chloride concentrations in freshwater can be toxic and lead to changes in organismal behavior, lethality, biotic homogenization, and altered food webs. High chloride concentrations have been reported for winter months in urban centers, as road density is highest in cities. However, summer chloride conditions are not typically studied as road salt is not actively applied outside of winter months, yet summer is when many taxa reproduce and are most sensitive to chloride. In our study, we test the spatial variability of summer chloride conditions across four watersheds in Toronto, Canada. We find 89% of 214 sampled sites exceeded the federal chronic exposure guidelines for chloride, and 13% exceeded the federal acute guidelines. Through a model linking concentration to cumulative proportion of impacted species, we estimate 34% of sites show in excess of one-quarter of all species may be impacted by their site-specific chloride concentrations, with up to two-thirds of species impacted at some sites. Our results suggest that even presumed low seasons for chloride show concentrations sufficient to cause significant negative impacts to aquatic communities.